WILD RELATIVES OF CULTIVATED PLANTS IN THE TERRITORY OF THE PRYAZOVSKY STATE NATURAL RESERVE - O. V. Zelenskaya; V. V. Korunchikova (Труды по прикладной ботанике, генетике и селекции)
The results of the research on tracing crop wild relatives in the territory of Priazovsky State Natural Reserve are presented. Specific composition of these plants, their habitats, ecological characteristics, the rank of affinity with cultivated plants, and their economic value have been studied. The possibility of conserving priority plant species within natural plant communities is discussed.